K.H ANWAR ZAHID DAKWAH METHODS; HADIST PERSPECTIVE - Amiliya, Lina (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Abstract: The various backgrounds of mad'u have made the method used by each da'i different in conveying his da'wah. One of them is the da'wah method carried out by KH Anwar Zahid. The purpose of this study was to determine the method of preaching KH. Anwar Zahid who is very humorous from the perspective of hadith. The research method is descriptive qualitative and library research. While the data analysis is data reduction, data presentation and drawing conclusions. The results of the study show that the da'wah method of KH Anwar Zahid from the perspective of hadith has relevance, including the da'wah method of wisdom contained in the hadith narrated by Bukhari Number 1800, which he applied in one of his lecture quotes about how to respond to the world wisely and wisely. The method of da'wah mauidzoh hasanah is contained in the hadith of Ahmad Number 21185, which he applied in one of his lecture quotes about happiness. The method of da'wah mujdalam hasanah is contained in the Tirmidhi hadith Number 1582, which he applied in one of his lecture quotes about the houses of the believers. And KH Anwar Zahid's preaching of humor is found in the hadiths of Thabrani and Baihaqi, which he applied in one of his lecture quotes about the mad'u he was dealing with at that time. Keywords: Da’wah Method, K.H Anwar Zahid, Hadith